Randomized clinical trial comparing liver resection with and without perioperative assessment of liver function. Issue 5 (14th June 2018) - Stockmann, M; Vondran, F W R; Fahrner, R; Tautenhahn, H M; Mittler, J; Bektas, H; Malinowski, M; Jara, M; Klein, I; Lock, J F; Pratschke, J; Chopra, S; et al.
Abstract: Background: Liver function tests may help to predict outcomes after liver surgery. The aim of this study was to evaluate the clinical impact on postoperative outcome and patient management of perioperative liver function testing using the LiMAx ® test. Methods: A multicentre RCT was conducted in six academic liver centres. Patients with intrahepatic tumours scheduled for open liver resection of at least one segment were eligible. Patients were randomized to undergo additional perioperative liver function tests (LiMAx ® group) or standard care (control group). Patients in the intervention arm received two perioperative LiMAx ® tests, one before the operation for surgical planning and another after surgery for postoperative management. The primary endpoint was the proportion of patients transferred directly to a general ward. Secondary endpoints were severe complications, length of hospital stay (LOS) and length of intermediate care/ICU (LOI) stay. Results: Some 148 patients were randomized. Thirty-six of 58 patients (62 per cent) in the LiMAx ® group were transferred directly to a general ward, compared with one of 60 (2 per cent) in the control group ( P < 0·001). The rate of severe complications was significantly lower in the LiMAx ® group (14 per cent versus 28 per cent in the control group; P = 0·022). LOS and LOI were significantly shorter in the LiMAx ® group (LOS: 10·6 versus 13·3 days respectively, P = 0·012; LOI: 0·8 versus 3·0 days, P < 0·001). Conclusion: Perioperative use of the LiMAx ® test improves postoperative management and reduces the incidence of severe complications after liver surgery. Registration number: NCT01785082 (https://clinicaltrials.gov ). Graphical Abstract: We performed a multicentre, randomized controlled trial to evaluate the impact of perioperative liver function assessment by the LiMAx ® test on postoperative outcome and patient management. Perioperative application of the LiMAx ® test in liver surgery improves postoperative management and reduces the incidence of severe complications. Liver function test helps to transfer the patient to the appropriate ward after hepatectomy